Effects of dietary β-glucan on growth rate, antioxidant status, immune response, and resistance against Aeromonas hydrophila in genetic improvement of farmed tilapia (GIFT, Oreochromis niloticus) - Xiaomei Dou; Han Huang; Ying Li; Junming Deng; Beiping Tan (Aquaculture Reports, 2023)
This study was conducted to assess the influences of dietary β-glucan on growth rate, antioxidant status, immunity response, and resistance against Aeromonas hydrophila of genetically improved farmed tilapia (GIFT, Oreochromis niloticus). Four isonitrogenous and isoenergetic diets were formulated to contain 0%, 0.2%, 0.4%, and 0.8% β-glucan, respectively. Fish with similar size (average body weight, 3.43 ± 0.02 g) were randomly distributed into 12 tanks with 40 juveniles per tank and hand-fed to apparent satiation twice daily for 10 weeks. The fish were then challenged by A. hydrophila and their cumulative survival rate was recorded for the next week. No obvious influences on growth rate and feed utilization of GIFT were induced by dietary β-glucan addition (P > 0.05). However, dietary 0.4% β-glucan inclusion increased the serum high-density lipoprotein cholesterol level but decreased the triglyceride, total cholesterol and low-density lipoprotein cholesterol levels as well as alanine aminotransferase and aspartate aminotransferase activities (P < 0.05). Similarly, the increased intestinal superoxide dismutase (SOD), peroxidase and total antioxidant capacity (TAC) activities as well as the decreased intestinal malondialdehyde (MDA) and reactive oxygen species contents were also observed in GIFT fed diet with 0.4% β-glucan (P < 0.05). Dietary addition of 0.8% β-glucan increased the plasma SOD, glutathione peroxidase (GPx), catalase, and TAC activities, but reduced the plasma MDA content (P < 0.05). Dietary β-glucan inclusion regardless of levels improved the hepatic SOD, glutathione reductase, catalase, peroxidase, TAC, and acid phosphatase activities, but depressed the hepatic nitric oxide and MDA contents (P < 0.05). Plasma lysozyme activity was improved by the inclusion of 0.4% and 0.8% β-glucan (P < 0.05); plasma immunoglobulin M, complement 3 and complement 4 contents were improved by dietary β-glucan inclusion (P < 0.05); respiratory burst activity of macrophages was improved by the addition of 0.2% β-glucan (P < 0.05). Additionally, dietary β-glucan supplementation reduced the mortality rate and increased the relative percentage survival of GIFT challenged by A. hydrophila (P < 0.05). These results indicated that suitable β-glucan inclusion (0.4–0.8%) could promote the antioxidant status, immune response and disease resistance of GIFT, and β-glucan can be used as a feed additive for GIFT.